Neonatal Mitral Valve Repair in Biventricular Repair, Single Ventricle Palliation, and Secondary Left Ventricular Recruitment: Indications, Techniques, and Mid-Term Outcomes - Myers, Patrick O.; Baird, Christopher W.; del Nido, Pedro J.; Pigula, Frank A.; Lang, Nora; Marx, Gerald R.; Emani, Sitaram M. (Frontiers in Surgery, 2015)
OBJECTIVES Although mitral valve repair is rarely required in neonates, this population is considered to be at high risk for adverse outcomes. The aim of this study was to review the indications for surgery, mechanisms, repair techniques, and mid-term outcomes of neonatal mitral valve repair. METHODS The demographic, procedural and outcome data were obtained for all neonates who underwent mitral valve repair from 2005 to 2012. The primary endpoints included mortality, transplantation and mitral valve reoperation. RESULTS Twenty patients were included during the study period. Median age at operation was 11 days (range 3-25). Eleven patients (55%) presented with mitral stenosis, 3 had regurgitation (15%), and 6 had mixed mitral disease (30%). Nineteen of 20 patients had mild or less regurgitation on immediate postoperative imaging. During a median follow-up of 5 months (1 month – 4.8 years), 6 patients died at a median of 33 months (7-41 months) from repair and one patient required orthotopic heart transplantation. Six patients required mitral valve reoperation, 5 for mitral valve re-repair and 1 for mitral valve replacement. Freedom from death, transplantation, or mitral valve replacement was 84.2±8.4% at 1 month, 71.3±11% at 6 months, 64.1±12% at 1 year and 51.3±15% at 2 years, and was worse for patients presenting with mitral regurgitation compared to stenosis or mixed mitral valve disease. CONCLUSIONS Although mitral valve repair can be performed with acceptable immediate postoperative result, this procedure carries a high burden of late death and mitral valve reoperations.